Construction of pY-Af Vector for Expression of Thermostable α-L-Arabinofuranosidase in Saccharomyces cerevisiae - Wirajana, I Nengah; Puspaningsih, Ni Nyoman Tri; Wasito, Eddy Bagus; Kusuma, Soekry Erfan; Kimura, Tetsuya; Sakka, Kazuo (Annales Bogorienses, 2010)
In this research, construction of expression vector for thermostable α-L-arabinofuranosidase in Saccharomyces cerevisiae BJ1824 was conducted. The Escherichia coli/S. cerevisiae shuttle vector, pYES2 was used as parental vector in construction. The abfA gene encoding α-L-arabinofuranosidase from Geobacillus thermoleovorans IT-08 was amplified by PCR, in which the plasmid pTP510 was used as a template. The amplification product was treated with SacI and XhoI and then subcloned to the pYES2 vector, which was previously digested with SacI and XhoI. The recombinant plasmid was designated as pY-Af and propagated first in E. coli Top10, and then transformed into S. cerevisiae BJ1824. For α-Larabinofuranosidase (AbfA) production, the yeast transformants were grown in YNBG selective medium and YPG rich medium, using galactose as an inducer. The AbfA activity was assayed by measuring the amount of p-nitrophenol (pNP) released from p-nitrophenyl-α-L-arabinofuranoside (pNPA) substrate at pH 6.0 and 70oC for 30 min. The recombinant AbfA activity was detected in either of culture medium (0.98%), cellassociated (14.17%) and intracellular (84.85%) when recombinant yeast was grown in YPG rich medium.